Coronavirus disease (COVID-19): A systematic review and meta-analysis to evaluate the impact of various comorbidities on serious events. Issue 5 (September 2020) - Nandy, Kunal; Salunke, Abhijeet; Pathak, Subodh Kumar; Pandey, Apurva; Doctor, Chinmay; Puj, Ketul; Sharma, Mohit; Jain, Abhishek; Warikoo, Vikas
Abstract: Background and aims: Currently there is limited knowledge on medical comorbidities and COVID-19; we conducted a systematic review and meta-analysis to evaluate the impact of various morbidities on serious events in COVID 19. Methods: PubMed, Cochrane Central Register of Clinical Trials were searched on April 28, 2020, to extract published articles that reported the outcomes of COVID-19 patients. The search terms were "coronavirus" and "clinical characteristics". ICU admission, mechanical ventilation, ARDS, Pneumonia, death was considered serious events. The comorbidities assessed in the study were Hypertension (HTN), Diabetes mellitus (DM), Cardiovascular diseases (CVD), Chronic obstructive pulmonary disease (COPD) and Chronic Kidney disease (CKD). Subsequently, comparisons between comorbidity patient group and the non-comorbidity patient groups, in terms of serious events were made using the pooled estimates of odd's ratio (OR) Results: We identified 688 published results and 16 studies with 3994 patients were included in the systematic review. Serious events were seen in 526(13.16%) patients. Presence of hypertension with OR 2.95, diabetes mellitus with OR 3.07, Cardio vascular disease with OR 4.58, COPD with OR 6.66 and Chronic kidney disease with OR 5.32 had significant association in patients with COVID 19 on having serious events. Presence of diabetes mellitus (OR 2.78)) had a significant impact on death in COVID 19 patients with a p-value 0.004. Conclusions: Presence of medical comorbidities in COVID-19 leads to higher risk of developing serious events i.e. ICU admission, mechanical intubation and mortality. The presence of Diabetes mellitus has a significant impact on mortality rate in COVID-19 patients. Highlights: Medical comorbidities in COVID-19 leads to higher morbidity and higher mortality rate. Patient with Comorbidities are likely to have high risk of severe events. Diabetes mellitus has a significant impact on mortality rate in COVID-19 patients.